Scalability of a robotic inspection and repair system - Ortega Jarrin, Washington Cristobal (Cranfield University, 2019)
Shift2Rail and In2Smart are two initiatives that will be part of the development of the necessary technologies to complete the Single European Railway Area (SERA). The target of this proposal is to accelerate the integration of new and advanced technologies into innovative rail product solutions. Shift2Rail has a robust framework to meet ambitious objectives. The most important is to double the capacity of the European rail system and increase its reliability and service quality by 50% while having life-cycle costs. In2Smart, as a project directed mainly of Network Rail, is measured in Technology Readiness Levels (TRL). These levels will indicate the maturity of technology for the application into the industry. The intention of this project is to reach a homogeneous TRL 3/4 demonstrator of a system capable to secure proper maintenance of rails, which is a Robotic Inspection and Repair System (RIRS). This research is focused on the scalability of the RIRS, taking into consideration the creation of a representative demonstrator that will authenticate the concept, the validation and verification of that demonstrator and finally the simulation of a scale-up system that will be more robust and will upgrade the TRL. This document contains the development of the control diagrams and schematics for the future incorporation of this control to a higher TRL prototype. The initial demonstrator consists of an autonomous railway vehicle equipped with a robotic arm that will scan the rails searching for faults and simulate a repairing process with a 3D printed polymer. The V&V of the physical demonstrator was a result of tests in the laboratory and the display of the demonstrator in several conferences and events.
Keywords: Shift2Rail; In2Smart; TRL; V&V; RIRS; autonomous; scalability